Tren Hijrah: Antara Fenomena Sosial dan Teologis Perspektif Muhammed Arkoun - Firmansyah, Firmansyah (TAJDID, 2021)
The recent hijrah trend is seen as a direct opposition to the allure of modernity, which is perceived as detrimental to the younger population. The emigration tendency among millennials has emerged as a significant social and theological issue. This research aims to examine the repercussions resulting from this movement. The research methodology employed is descriptive qualitative. The research findings indicate that the trend battle will persist, contingent upon the prominent issues in social media discussions. Specifically, when examining the hijrah movement from Arkoun's theological perspective, three layers emerge that encompass reasoning, leading individuals to feel content with their own truth.